Analisis Pengaruh Pelaksanaan Standar Pelayanan Kefarmasian Terhadap Kepuasan Pasien Pada Program Rujuk Balik di Kota Yogyakarta - Dwi R, Novi; Satibi; Ayu P, Diah (Jurnal Farmasi (Journal of Pharmacy), 2015)
The Pharmaceutical services standards as an implementation reference of Pharmaceutical services in the pharmacy is intended to improve the quality of pharmaceutical services. Referral program is one BPJS health program for people with chronic diseases. The drugs for this program are taken in pharmacies outside the capitation fee system claims. The Quality of services affects patient satisfaction. Individual characteristics associated with satisfaction. This study aims to determine the effect of the implementation of the standard pharmaceutical services on the satisfaction and the relationship between the characteristics and the patient satisfaction in the pharmacies in the Referral Program. This research is descriptive analytic method of data collection is done by survey. Data obtained through a questionnaire which contains characteristics of respondents, respondents' perceptions of the implementation of pharmaceutical service standards and satisfaction. The research is supported with qualitative data as the results of interviews about opinions and input. The location of the research is in referral pharmacy in Yogyakarta with the samples as many as 101 respondents that were divided proportionally. There is the influence of the standard implementation of pharmaceutical services to the satisfaction of the patient in the pharmacy at Referral Program. Significant influence on the clinical aspects of pharmaceutical services (p = 0.000) and pharmaceutical esource (p=0.000) while the aspects of the supplies management were not significant (p = 0.436). Patient characteristics associated with the satisfaction were age and the distance between the residence and the pharmacy, while the characteristics of gender, education, employment, disease were not related with the patient satisfaction.